Postmenopausal breast cancer and occupational exposure to chemicals - Cecilia Videnros; Jenny Selander; Pernilla Wiebert; Maria Albin; Nils Plato; Signe Borgquist; Jonas Manjer; Per Gustavsson (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: The aim of this study was to investigate if exposure to chemicals in the workplace was associated with an increased risk of postmenopausal breast cancer. METHODS: The study comprised women born 1923-1950 living in Malmö city, Sweden, 1991-1996, and enrolled for a prospective population cohort study. Occupational exposure to various chemicals was assessed from job-exposure matrices. An extensive set of individual data on hormonal breast cancer risk factors were collected via a baseline questionnaire and used for confounding control. First time diagnoses of invasive breast cancer were identified through the Swedish Cancer Registry until end of follow-up on 31 December 2013. RESULTS: Of 16 084 women, 1011 were diagnosed with breast cancer. Women exposed to chemicals in their occupational environment had a statistically significant increased risk [adjusted hazard ratio (HR_adj) 1.26, 95% confidence interval (CI) 1.02-1.54] of breast cancer, and the risk correlated with duration of exposure. Investigation of risk in association with specific chemicals showed a non-significantly elevated risk after exposure to organic solvents. More than ten years of exposure to diesel exhaust was associated with an increased risk (HR_adj 1.69, 95% CI 1.01-2.82). Occupational chemical exposures account for 2% of the breast cancer cases in this population. CONCLUSIONS: Occupational exposure to chemicals in general was associated with an elevated risk of breast cancer. A slight elevation of risk was seen after exposure to organic solvents. A statistically significant elevation of risk after >10 years of exposure to diesel exhaust was an unexpected finding.